(untitled) (Journal of Philosophy Culture and Political Science, 2015)
The problems of the religious consciousness considered in the article as from times before our era before present-day time. The religious consciousness is part of public consciousness and there is opinions that it rises the interpersonal communication. The worldoutlook and faith forms the base to internal spiritual life to personalities and is defined by external nature of the person. A finder of the larval development and directivities is in the religions faith. The Faith in the Tengri and Umay, worship spirit their own limit, development of the Islam and shamanism defines the particularities of the culture, religious of worldoutlook and psychological distinctive quality of kazakh folk. In article is spoken about that analysis of the behavior of the person follows to begin from his faith. The beliefs ed with old times before our days, have not lost its unique. So presently it is necessary deeply and all round research shaping and particularities of the development of the religious consciousness in kazakh society.